2005
DOI: 10.1021/ja0452166
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Dependent Modulation of a Pathogen Response in Plants by Synthetic O-Antigen Polysaccharides

Abstract: Many phytopathogenic bacteria display lipopolysaccharides (LPS) with the O-chain repeating unit [alpha-l-Rha-(1-->3)-alpha-l-Rha-(1-->3)-alpha-l-Rha-(1-->2)](n)(). This trisaccharide unit was synthesized and oligomerized to obtain hexa- and nonasaccharides. The deprotected rhamnans were effective in suppressing the hypersensitive response (HR) and in inducing PR-1 gene expression in Arabidopsis thaliana. Conformational analysis of the oligorhamnans by NMR spectroscopy and molecular dynamics calculations reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
60
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 12 publications
3
60
0
Order By: Relevance
“…They demonstrated that short oligosaccharides can induce the expression of defense-related genes and prevent HR in a size-dependent manner. Therefore, they proposed that the coiled structure exposed from dimeric and trimeric oligomers of the repeating unit 2)] n , peculiar for many O-chains of phytopathogenic bacteria, will act as a PAMP, being recognized by plants and consequently eliciting specific responses, including HR suppression and PR1 gene expression (58).…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that short oligosaccharides can induce the expression of defense-related genes and prevent HR in a size-dependent manner. Therefore, they proposed that the coiled structure exposed from dimeric and trimeric oligomers of the repeating unit 2)] n , peculiar for many O-chains of phytopathogenic bacteria, will act as a PAMP, being recognized by plants and consequently eliciting specific responses, including HR suppression and PR1 gene expression (58).…”
Section: Discussionmentioning
confidence: 99%
“…This has also been demonstrated for flagellin, the protein subunit that builds up bacterial flagella: whereas the Arabidopsis flagellin receptor FLS2 recognizes the very conserved peptide Flg22, which is part of the so called Spike region of bacterial flagellin, a more central hypervariable peptide in the D1 region acts as PAMP in mammals (7,73,74). Moreover, in mammals lipid A as the invariable part of LPS is the most potent stimulator of innate immunity (75,76), whereas Arabidopsis perceives LPS via both the lipid A part as well as synthetic oligorhamnans, which are commonly found in the highly variable O-antigen of LPS (36,77). We suggest a model in which PGN was chosen as non-self determinant both in plants and animals because of its characteristics as a typical PAMP: it is widely found in bacteria, structurally stable, displayed on the cell surface and not found in eukaryotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings have suggested that the lipid A moiety may be at least partially responsible for LPS perception by Arabidopsis thaliana, leading to a rapid burst of NO, a hallmark of innate immunity in animals (9). Using synthetic O-antigen polysaccharides (oligorhamnans), it has been shown that the O-chain of LPS is recognized by Arabidopsis and that this recognition leads to elicitation of a specific gene transcription response associated with defense (10). These observations, together with the established influence of the core region on lipid A toxicity in animals, indicate that the elucidation of the structure and of the biological activity of both lipid A and core region are of high importance for a better understanding of LPS action in plants.…”
mentioning
confidence: 99%